Time to Achieve Target Mean Arterial Pressure during Resuscitation from Experimental Anaphylactic Shock in an Animal Model. A Comparison of Adrenaline Alone or in Combination with Different Volume Expanders. Issue 6 (November 2013) - Tajima, K.; Zheng, F.; Collange, O.; Barthel, G.; Thornton, S. N.; Longrois, D.; Levy, B.; Audibert, G.; Malinovsky, J. M.; Mertes, P. M.
Anaphylactic shock is a rare, but potentially lethal complication, combining life-threatening circulatory failure and massive fluid shifts. Treatment guidelines rely on adrenaline and volume expansion by intravenous fluids, but there is no solid evidence for the choice of one specific type of fluid over another. Our purpose was to compare the time to achieve target mean arterial pressure upon resuscitation using adrenaline alone versus adrenaline with different resuscitation fluids in an animal model and to compare the tissue oxygen pressures (PtiO2 ) with the various strategies. Twenty-five ovalbumin-sensitised Brown Norway rats were allocated to five groups after anaphylactic shock induction: vehicle (CON), adrenaline alone (AD), or adrenaline with isotonic saline (AD+IS), hydroxyethyl starch (AD+HES) or hypertonic saline (AD+HS). Time to reach a target mean arterial pressure value of 75 mmHg, cardiac output, skeletal muscle PtiO2, lactate/pyruvate ratio and cumulative doses of adrenaline were recorded. Non-treated rats died within 15 minutes. The target mean arterial pressure value was reached faster with AD+HES (median: 10 minutes, range: 7.5 to 12.5 minutes) and AD+IS (median: 17.5 minutes, range: 5 to 25 minutes) versus adrenaline alone (median: 25 minutes, range: 20–30 minutes). There were also reduced adrenaline requirements in these groups. The skeletal muscle PtiO2 was restored only in the AD+HES group. Although direct extrapolation to humans should be made with caution, our results support the combined use of adrenaline and volume expansion for resuscitation from anaphylactic shock. When used with adrenaline the most effective fluid was hydroxyethyl starch, whereas hypertonic saline was the least effective.